PTH-119 International multicentre study of mallory weiss tear related gi bleeding: demographics, endoscopic therapy and outcome. (8th June 2018) - Lynch, Lucy; Laursen, Stig Borbjerg; Laine, Loren; Dalton, Harry; Michell, Nick; Ngu, Jeffery; Schultz, Michael; Stanley, Adrian
Abstract : Introduction: Mallory Weiss tears (MWT) are relatively uncommon causes of upper GI bleeding (UGIB) and patients with these lesions are generally considered at low risk of poor outcome. However there are relatively limited data on this condition. In addition, there is uncertainty about which patients with MWT require endoscopic therapy and which modality should be applied. We aimed to describe an international cohort of patients presenting with UGIB secondary to MWT, including the endoscopic therapy undertaken. We also compared clinical outcomes between patients with MWT and other causes of UGIB. Methods: From an international dataset of consecutive patients undergoing endoscopy for acute UGIB at six hospitals in UK, Denmark, USA, Singapore and New Zealand, we assessed those patients with MWT bleeding, including the estimated Forrest classification and endoscopic therapy applied. We also compared baseline factors, rebleeding rates and 30 day mortality between patients with MWT, peptic ulcer bleeding (PUB) and all cause UGIB. Results: Patients with MWT bleeding were younger, with higher baseline pulse and Hb compared to those with PUB and all cause UGIB. Although the rebleeding rate was lower in MWT patients compared with PUB patients, mortality was similar (table 1). Most MWT lesions were Forrest 1a or 3 at endoscopy (table 2). 42 (43%) MWT patients received endotherapy. 38 (90%) had adrenaline injection, 21 (50%) clips, and 5 (12%) thermal probe applied. 22 (52%) treated patients had combination therapy. Overall rebleeding rate for MWT patients was 4.1% (1.8% in those not treated and 7.1% in those treated with endotherapy). Conclusions: Although patients presenting with MWT were younger, with lower rebleeding rate compared with PUB, their mortality was similar to that of patients with PUB and all cause UGIB. Endoscopic therapy was applied to 43% MWT patients, with adrenaline injection, followed by clips, the most common modalities employed.